Governance, risk and compliance - Barthel, Amalia (Henry Stewart Talks, 2019)
Enterprise risk management, IT related risk, Government and risk management, Risk governance frameworks, How IT can support corporate governance, Compliance, Demonstrating adherence to laws, regulations, policies and procedures, Critical infrastructure and cybersecurity, Metrics for performance and conformance